2020
DOI: 10.1038/s12276-020-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of endothelial calpain knockout in lipopolysaccharide-induced acute kidney injury via attenuation of the p38-iNOS pathway and NO/ROS production

Abstract: To explore the role of calpain and its signaling pathway in lipopolysaccharide (LPS)-induced acute kidney injury (AKI), animal models of endotoxemia were established by administration of LPS to mice with endothelial-specific Capn4 knockout (TEK/Capn4 −/− ), mice with calpastatin (an endogenous calpain inhibitor) overexpression (Tg-CAST) and mice with myeloid-specific Capn4 knockout (LYZ/Capn4 −/− ). Mouse pulmonary microvascular endothelial cells (PMECs) were used as a model of the microvascular endothelium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…It has been shown that treatment with septic plasma from endotoxemic mice increased calpain enzyme activity in cultured pulmonary microvascular ECs and caused EC apoptosis ( 55 ). In addition, EC-specific deletion of calpain showed protective effects on LPS-induced kidney injury ( 56 ), indicating that calpain activation plays a regulatory role in endothelial injury during inflammation. However, whether calpain could directly disrupt the endothelial barrier by targeting VE-cadherin–mediated adherens junction remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that treatment with septic plasma from endotoxemic mice increased calpain enzyme activity in cultured pulmonary microvascular ECs and caused EC apoptosis ( 55 ). In addition, EC-specific deletion of calpain showed protective effects on LPS-induced kidney injury ( 56 ), indicating that calpain activation plays a regulatory role in endothelial injury during inflammation. However, whether calpain could directly disrupt the endothelial barrier by targeting VE-cadherin–mediated adherens junction remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The activated p38 MAPK pathway promoted the process of kidney injury 52–54 . Melamine have been reported to activate the phosphorylation of p38 to induce apoptosis in rats renal tubular epithelial cells, 55 and increase the risk of forming kidney stone in rats 56 .…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling pathways are well studied and involved in various cellular processes, including cell inflammation, apoptosis, differentiation and proliferation 48 , 49 , which are also evident in kidney injury 50 . The P38 MAPK/JNK pathways can modulate the expression of the apoptotic proteins Bax and Bcl-2, which is mediated by oxidative stress-induced renal damage 47 , 51 , 52 . In the present study, we found that kidney injury is related to VCM-induced oxidative stress, apoptosis and the expression of the apoptosis-related genes Bax and Bcl-2, as well as P38 MAPK/JNK phosphorylation were found to be significantly upregulated but were decreased by the antioxidants NAC and vitamin C. Our results indicated that the P38 MAPK/JNK pathways are involved in the protective effect of NAC against VCM-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%